PENGARUH LIKUIDITAS, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN LAPORAN KEUANGAN - Yuniarsyah, Dwi Harista (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
This main aims of this study is to test the influence of liquidity, profitability, and firm size to the disclosure of financial statement. The sampels are 23 companies which have been selected by using purposive sampling from banking companies which are listed in Indonesia Stock Exchange from 2010 to 2012. The financial statement data of banking industries have been obtained from âSTIESIAâ Indonesia Stock Exchange Investment Galery on Jalan Menur Pumpungan 30 Surabaya and from IDX official website www.idx.co.id. The result of the reseach shows that: (1) liquidity has no significant influence to the disclosure of financial statement, (2) profitability has no significant influence to the disclosure of financial statement, and (3) firm size has significant influence to the disclosure of financial statement.Keywords: Liquidity, Profitability, Firm Size, and the Disclosure of Financial Statement